Magmaris: a new generation metallic sirolimus-eluting fully bioresorbable scaffold: present status and future perspectives - Rapetto, Claudio (J Thorac Dis, 2017)
Drug-eluting stents (DES) have reached a high safety and efficacy profile, becoming the best option for percutaneous coronary interventions (PCI) based revascularization. However, despite their optimal performance, a few concerns remain regarding their use, mainly due to permanent caging of the vessels and its consequences, first of all late stent thrombosis (ST). Bioresorbable scaffolds (BRS) aim to overcome these issues. The results achieved in randomized controlled trials (RCT) by the first generation of poly-L-lactic acid (PLLA) based scaffolds were promising at 1 year, but the first long term reports (albeit flawed by non-optimal implantation technique) have been disappointing, showing, for instance, an increased risk of ST and target vessel myocardial infarction (TV-MI). In such a scenario the advent of a newer generation magnesium (Mg) based BRS is welcome, mainly because of its innovative mechanical and chemical features coupled with well proven biocompatibility. Despite being in its infancy, this technology seems to promise a great potential. In our article, we review the Magmaris (Biotronik AG, Bülach, Switzerland) Mg BRS development from animal models to human use, underscore its best qualities and weaknesses, and provide hints of its possible future perspectives.